أثر الاقتصاد غير الرسمي على التشغيل في الجزائر: دراسة تقيمية للفترة 1990-2017 - بقاط, حنان (جامعة الوادي - University of Eloued, 2017)
تهدف هذه الورقة الى عرض أهم مفاهيم الاقتصاد غير الرسمي وطرق تقدير حجمه بالإضافة الى دراسة واقع هذه الظاهرة في الجزائر ومكانتها في سوق العمل خلال الفترة 1990 إلى غاية 2017. ومن خلال الدراسة استخلصنا أن الاقتصاد غير الرسمي في الجزائر يأخذ حيزا هاما من النشاط الاقتصادي فمن خلال تقديرات الديوان الوطني للاحصائيات و معطيات المجلس الاقتصادي والاجتماعي تراوح حجم الاقتصاد غير الرسمي بين 30% الى 50% من اجمالي الناتج المحلي ويوفر مناصب شغل هامة تتجاوز 45% من اجمالي التشغيل تتوزع هذه المناصب على عدة قطاعات أهمها قطاع التجارة والخدمات و قطاع البناء والاشغال العمومية Abstract: This paper aims to present the most important concepts of the informal economy And methods of estimating its size and in addition to studying the situation of this phenomenon in Algeria And its position in the job market during the period of 1990 to 2017. Through the study we concluded that the informal economy in Algeria Takes an important place of economic activity through the National Bureau of Statistics and the Economic and Social Council, The size of the informal economy ranged from 30% to 50% of GDP And provides significant job positions exceeding 45% of total employment, These positions are spread across several sectors Most notably the trade and services sector And construction and public works.
The impact of the informal economy on employment in Algeria Evaluation study for the period 1990-2017
مقال بمجلة الدراسات المالية والمحاسبية . مج 08 ع01. جوان 2017 . جامعة الوادي
Keywords: الاقتصاد غير الرسمي، سوق العمل، التشغيل غير الرسمي; Informal economy, job market, informal employment